THE SIGNIFICANCE OF UNDERSTANDING POLYSEMY AND MEANING (Лучшие интеллектуальные исследования, 2025)
Аbstrаct:  This article offers a thorough examination of polysemy, a fundamental linguistic phenomenon in which a single lexical term has several related meanings.  Polysemy is a reflection of how human intellect arranges and understands the world, in addition to being a characteristic of ordinary language use.  In order to provide insights into how meanings are expanded and organised within the mental lexicon, the study looks at the theoretical underpinnings of polysemy from both structuralist and cognitive linguistic perspectives.  There is a strong differentiation between polysemy and related semantic issues like ambiguity and homonymy.  Using examples from English and other languages, the paper also examines how context affects the intended meaning of polysemous terms.Furthermore, the useful applications of polysemy are examined in fields including natural language processing, lexicography, translation, and language instruction.  This work advances our knowledge of semantics and the intricacies of human language by illuminating the changing nature of word meaning.